(untitled) (Zoo Botanica, 2025)
This study is the first comprehensive Morpho-meristic study of Heteropneustes fossilis from two distinct locations along the length of river Kabul; Shalman valley and Michini. For this purpose, a total of 20 fish specimens were collected from April to July 2025. Various fishing equipment were employed for catching the fish. The collected fish specimens were identified their meristic characters and morphometric measurements were recorded and finally preserved in ethanol. Fin rays were observed using a magnifying glass and stereo microscope. Body weight (BW) and morphometric measurements were recorded with a digital balance and caliper, with an accuracy of 0.01 g and 0.01 cm, respectively. The specimens showed a moderate variation in total length (15.0-18.2 cm) and body weight (37.3-42.0 g). Statistical analysis of the observed characters, including assessment of length-weight relationships (LWRs) and length-length relationships (LLRs) were done utilizing the software Prism. The fin formula observed for H. fossilis was: D. 5-7, P. 1/6-7, V. 6, A. 64-69, C. 18-22. LWRs between BW and most length parameters were significant (p < 0.001; r² = 0.94), except for Post dorsal length (p > 0.05). The growth pattern exhibited a negative allometric growth (b < 3) potentially due to restricted food supply, environmental stress and reproductive activity. LLRs were statistically significant (p < 0.001; r² = 0.98). These findings report the species for the first time from Shalman valley and provide key baseline data for species identification, which might be helpful in the conservation of H. fossilis within the River Kabul ecosystem